A hybrid magnetic core–shell fibrous silica nanocomposite for a chemosensor-based highly effective fluorescent detection of Cu(ii). Issue 72 (27th September 2017) - Radhakrishnan, K.; Panneerselvam, P.; Ravikumar, A.
Abstract : Herein, a novel hybrid magnetic core–shell fibrous silica nanocomposite (RhB–Fe3 O4 /MnO2 /SiO2 /KCC-1) probe-based chemosensor was designed and its behaviour towards Cu(ii ) metal ion was investigated using a fluorescence spectrometer. Abstract : Herein, a novel hybrid magnetic core–shell fibrous silica nanocomposite (RhB–Fe3 O4 /MnO2 /SiO2 /KCC-1) probe-based chemosensor was designed and its behaviour towards Cu(ii ) metal ion was investigated using a fluorescence spectrometer. The organic receptor rhodamine B (RhB) fluorophore derivative was covalently grafted onto the surface of the magnetic core–shell fibrous silica nanocomposite. This sensing probe achieved the selectivity towards Cu(ii ) in an aqueous solution, and other competing metal ions basically induced no spectral change. Thus, this sensing probe can work as a Cu(ii ) selective fluorescent sensor. The synthesized material was characterized using transmission electron microscopy (TEM), scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS), surface analysis (with BET), Fourier transform infrared spectroscopy (FT-IR), X-ray diffractometry, and thermogravimetric analysis (TGA). The rhodamine B derivative has a unique signalling probe that exhibits a turn-on fluorescence enhancement upon the recognition of Cu(ii ) ion with an excitation at 569 nm. The linearity of the Stern–Volmer plot ( R 2 = 0.9882) and the detection limit of 12.3 × 10 −8 M were achieved. Finally, the sensor was tested to detect Cu(ii ) ion in different real water samples.